2020
DOI: 10.1002/14651858.cd006237.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve return to work in depressed people

Abstract: Analysis 2.3. Comparison 2 Work-directed plus clinical versus clinical alone (long term), Outcome 3 Work functioning. Analysis 3.1. Comparison 3 Work-directed plus clinical versus work-directed (medium term), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(183 citation statements)
references
References 187 publications
7
156
0
7
Order By: Relevance
“…Some of the studies named PST in the earlier meta-analyses have been grouped RTW-I in the present since they had a clear RTW-focus. In the earlier meta-analyses, there was no group reflecting the RTW-focus (Arends et al 2012; Nieuwenhuijsen et al 2014). As in previous studies, this meta-analysis showed generally small effects on sick leave, but there was a significant effect on sick leave when comparing all interventions to CAU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies named PST in the earlier meta-analyses have been grouped RTW-I in the present since they had a clear RTW-focus. In the earlier meta-analyses, there was no group reflecting the RTW-focus (Arends et al 2012; Nieuwenhuijsen et al 2014). As in previous studies, this meta-analysis showed generally small effects on sick leave, but there was a significant effect on sick leave when comparing all interventions to CAU.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these meta-analyses are thus somewhat inconsistent, but as additional studies are published in a rapid pace further systematic reviews and meta-analyses are warranted to investigate the effect of psychological treatments on sick leave. In addition, two of the prior meta-analytic studies included solely depression (Nieuwenhuijsen et al 2014) or adjustment disorder (Arends et al 2012) respectively, and not the whole spectrum of CMDs, which could have reduced statistical power in previous studies. A third meta-analysis restricted outcomes to the proportion of employees who returned to work after the intervention and time until full RTW (Nigatu et al 2016), which might exclude studies with other relevant measures of sick leave and RTW.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation services serve PMIs better when they are integrated with clinical services. 13 , 17 , 18 Thus, changes in rehabilitation must parallel corresponding changes in mental health care delivery. Some areas in which telerehabilitation may play a role are as follows: Telemedicine Telepsychotherapy Telepsychiatric social work and liaison Supervision of home-based rehabilitation Training and mentoring of grassroots workers by experts …”
Section: Role Of Telerehabilitationmentioning
confidence: 99%
“…Common mental disorders such as depression, anxiety and stress disorders are frequent causes of sick leave in high-income countries, including Denmark [ 1 2 3 4 ]. In Denmark, common mental disorders are the main reason for early retirement [ 2 5 ], and anxiety and depression alone account for annual production losses of 1.6 billion Euros (2010–2012 price levels) caused by absence from the labour market due to sick days, early retirement benefits and early death [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with common mental disorders who want to keep, return to or find a job often have a combination of social problems and health issues that call for integration of public services but are often met with fragmented and uncoordinated services [ 6 ]. Research has shown that adequate mental health care cannot stand alone when supporting people in returning to work [ 4 ]. Integration of health care and vocational services has shown to improve return to work for people with severe mental disorders [ 7 8 ].…”
Section: Introductionmentioning
confidence: 99%